Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 463: 116



Work Step by Step

$7x^{4}+34x^{2}-5$ ... Searching for two factors of $ac=-35$ whose sum is $b=34,$ we find$\qquad 35$ and $-1.$ Rewrite the middle term and factor in pairs: $=7x^{4}+35x^{2}-x^{2}-5=$ $=7x^{2}(x^{2}+5)-(x^{2}+5)$ =$(x^{2}+5)(7x^{2}-1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.